What do we know about the possibility of predicting the potential efficacy and safety of methotrexate, by measuring the concentration of its metabolites in rheumatoid arthritis? - G. I. Gridneva; E. S. Aronova; V. S. Sygyrta; A. V. Kudryavtseva; K. S. Nurbaeva (Современная ревматология, 2020)
Rheumatoid arthritis (RA) is characterized by a progressive course with the formation of joint deformities and the development of severe functional disorders. The most favorable conditions for changing the course of the disease emerge in the first months after its onset. Methotrexate (MTX) occupies a leading position in the treatment of RA. There is a need to develop tools that will be able to predict the efficacy and tolerability of MTX at the earliest stages of RA treatment. The concentration of active metabolites of MTX is considered as a potential biomarker that enables one to predict what response to therapy with this drug will be.The paper analyzes the most relevant works devoted to the study of the concentration of active MTX metabolites polyglutamates (MTX PGs) in patients with RA. It is shown that the presented studies do not cover all the possibilities of therapeutic drug monitoring, in particular the determination of the levels of MTX PGs in mononuclear cells over time. Further investigation is needed to develop an objective approach to prescribing MTX in RA patients.